A Highly Abundant Lectin Protein in Arabidopsis thaliana Confers Resistance Against Pathogens - Maria prihtamala Omega; Skye Thomas Hall; Peer Schenk; Bostjan Kobe (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2008)
Lectins are glycoproteins that recognize and bind to specific carbohydrates. they are involved in a range of biological functions, such as plant defence, storage proteins seed germination and plant microbe interactions. Lectin 3.1 (At3g 15356) is a protein in plant model , Arabidopsis thaliana, that has been shown to be up-regulated in all defence pathways, especially in responce to methyl ester jasmonate (MJ) . All thal was known about the gene was that it had good homology to the beta domain of legume lectins. That aim of this project was to characterize the structure and function of the Iectin protein using CD spectra and X-ray crystallography. A TDNA insertion line for the lectin gene and a number of 35S over-expression lines that had varying levels of expression had been generated, but none of these showed any obvious phenotype. Two protein bands were observed on Comassie stained SDS-PAGE gels in the over-expression lines and in MJ induced wild-type (WT) . The two protein bands represented two isoforms of the lectin 3.1 protein ; in a glycsylation assay the larger protein band was shown to be heavily glycosylated . A nematode (M. incognita) disease assay djscovered that the lectin over-expression lines had less nematode eggs compared to that of the WT and that the insertion line had more nematode eggs than the WT. This data provides evidence that lectin 3. 1 improves. plant resistance against M. incognita infection. interestingly, the nematode gut lining contains fucose with which Iectin 3.1 binds to. Keywords: Arabidopsis thaliana, lectin’s structure and function, pathogen resistance